Thrombin-activatable fibrinolysis inhibitor (TAFI): a novel predictor of angiographic coronary restenosis - Lau, Herbert K.; Segev, Amit; Hegele, Robert A.; Sparkes, John D.; M.Teitel, Jerome; Chisholm, Robert J.; Strauss, Bradley H. (Thrombosis and Haemostasis, 2003)
The fibrinolytic system is closely related to several processes that are involved in restenosis. We previously showed that low PAI-1 plasma levels predicted restenosis. Recently, a different fibrinolytic inhibitor, TAFI, has been described. The aims of this study were to evaluate the relationship between pre-procedural plasma levels of TAFI and late angiographic restenosis and the interaction between TAFI and PAI-1. We prospectively studied 159 patients with stable angina who underwent successful elective angioplasty or stenting of de novo native coronary artery lesions. TAFI and PAI-1 antigen levels were measured in plasma samples drawn before the procedure. Follow-up coronary angiography was performed in 92% of patients. There was a significant correlation between pre-procedural TAFI levels and 6-month % diameter stenosis (DS) (r = 0.21; p = 0.013). The overall angiographic restenosis rate (DS>50%) was 31%. Pre-procedural TAFI levels were significantly higher in patients with restenosis (108 ± 33% versus 94±30%, p = 0.011). Restenosis rates for patients in the upper tertile of TAFI levels were 2-fold higher than for those in the lowest tertile (45% versus 22%; p = 0.016). A combination of high TAFI and low PAI-1 levels identified patients at the highest risk of restenosis (53%) compared to 14% in patients with low TAFI and high PAI-1 levels; p = 0.027. In conclusion, pre-procedural plasma TAFI antigen levels identify patients at increased risk for restenosis after PCI.
Keywords: TAFI; PAI-1; restenosis; fibrinolysis